Analysis of methods for assessing the aiming process in biathlon shooting - Heller, M.; Baca, A.; Kornfeind P.; Baron, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
In rifle shooting disciplines coaches and athletes are interested in the motion of the rifle just before and immediately after shooting. Normally, commercial laser systems (e.g. Noptel, Finland) are used to measure and store the hit point of the shot and the on-target trajectory of the alignment of the weapon. A major drawback of this method lies in the necessity of attaching the laser device to the rifle. The purpose of this study was to analyse the usefulness of a video-based system developed by Baca & Kornfeind (2006), which is able to track the 2D-movement of the muzzle of the weapon automatically. The results show considerable correspondence of the on-target-trajectory and the 2Dmovement of the muzzle, in particular in vertical direction. However, translation movements of the shoulder during aiming, which are rather difficult to diagnose, may cause differences in the horizontal plane. KEY WORDS: feedback system, aiming process, biathlon, shooting.